THE EFFECTS OF CRIME ACTIVITIES ON TOURISM INDUSTRY: EMPIRICAL EVIDENCE FROM KWAZULU-NATAL PROVINCE, SOUTH AFRICA - Madiseng Messiah Phori; Prof W Maluleke; Dr K Phalane (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study focuses on crime activities on tourism industry, focusing on KwaZulu-Natal (KZN) Province, Durban of South Africa. The main objective of this study was to determine the effects of crime on tourism within the identified study area. This study adopted the empirical research design, aided with qualitative research approach. Three (03) Law Enforcement Agencies (LEAs) and 03 business owners were purposively selected to form part of structured Key Informant Interviews (KIIs) for data collections. The results indicate that although mechanisms to combat crimes in the KZN Province, Durban inner city specifically, various crimes continue to occur, these pose uncontrollable threats and strongly dents this industry. It was also revealed that visitors reluctantly revisit Durban after witnessing robbery and other scenes of criminal acts and the selected businesses either face closure or relocation, this often result to these businesses suffer detrimental financial losses. Therefore, this study recommends that tourism industry, including business communities in Durban inner city, as well as hospitality sector and public members should work urgently collaborate to find innovative lasting solutions. It is also necessary to bolster the local South African Police Service Visible Police (SAPS VISPOL), for patrolling and offering efficient plans ahead to control large crowds at popular holiday spots in Durban. The coordination between Durban's tourism industry and LEAs remains essential to improve existing crime combating, investigation and prevention methods.